Soft tissue complications and timing of surgery in patients with a tongue-type displaced intra-articular calcaneal fracture: An international retrospective cohort study. Issue 2 (February 2018) - De Boer, A. Siebe; Van Lieshout, Esther M.M.; Van 't Land, Freek; Misselyn, Dominique; Schepers, Tim; Den Hartog, Dennis; Verhofstad, Michael H.J.
Abstract: Introduction: Tongue-type displaced intra-articular calcaneal fractures (DIACF) are associated with a specific pattern of fracture displacement in contrast to joint depression fractures. This may result in tension of soft tissue in the posterior part of the heel. Tension-induced ischemia can result in skin necrosis. The objectives of this study were to investigate whether patients with tongue-type calcaneal fractures exert a higher risk of complications, especially of the posterior soft tissues, than joint depression type fractures. Also, late interventions ( e.g., antibiotics, debridements, and amputations) and the effect of timing of surgery on the complication rate was assessed. Methods: In this international retrospective cohort study, data of adult patients with a DIACF in the period January 1, 2005–December 31, 2015 were extracted from patients' medical files. Descriptive, univariate, and multivariable analyses were performed in SPSS. Results: A total of 560 patients with 632 DIACF were included (295 tongue-type and 337 non-tongue-type fractures). At hospital presentation, 20.3% of the patients with a tongue-type fracture had compromised posterior soft tissue versus 12.8% with non-tongue-type fractures (p = 0.032). However, corrected for potential confounders the risk was no longer statistically significant (OR 1.497; 95% CI 0.831–2.696). Patients with a TT-DIACF had a 1.2–3.4-fold higher rate of any local wound complication (deep infections, and full thickness lesions, p < 0.03). In addition they had 2.0–8.0-fold more intravenous antibiotics, debridements, soft tissue coverage procedures and amputations (p < 0.03). Patients who underwent surgery within two days after trauma had a higher risk to develop any complication, in particular superficial infections, when compared to surgery between 3–7 days, but no significant difference between 3 and 7 and ≥8 days could be demonstrated. Conclusion: Despite the fact that patients with a tongue-type fracture developed posterior skin and soft tissue compromise nearly twice as often, this difference disappeared after correction for confounders. The overall complication risk was increased in patients with tongue-type calcaneal fractures as compared to patients with a non-tongue-type fracture. Whether or not patients with tongue-type fractures require immediate surgery cannot be concluded from the data.